POTENSI PANTAI SIBOLO PULAU-PULAU BATU NIAS SELATAN UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN - Bantors Sihombing; Erlin Kuswindayani Bawaulu (Jurnal Ilmiah Akomodasi Agung, 2020)
This study, entitled The Tourism Potential of Sibolo Beach, Batu Islands, South Nias Regency to Increase Tourist Visits, discusses how the potential of Sibolo beach to attract tourist visits. Qualitative descriptive research method. The informants of this research are the people of Sibolo beach, tourists, and the staff of Pinnacles North Telo who are the managers of the Sibolo beach. The results show that Sibolo beach has sufficient potential to be visited by tourists but does not have complete facilities and infrastructure such as tourist information centers, money changers, souvenir shops or local craft centers and the lack of skilled human resources in the tourism sector. Promotions that have not been carried out optimally and only use a few promotional strategies and the incessant efforts made by the manager of the object and tourist attraction of Sibolo beach in increasing tourist visits.